LEACHING KINETICS OF ULEXITE ORE IN AQUEOUS MEDIUM AT DIFFERENT CO2 PARTIAL PRESSURES - Elcicek, Huseyin; Kocakerim, Mehmet M. (BRAZILIAN SOC CHEMICAL ENG, 2018)
This manuscript presents a study regarding the leaching kinetics of ulexite (Na2O.2CaO.5B(2)O(3)center dot 16H(2)O) under different CO2 partial pressures in aqueous media. The effects of the reaction temperature, particle size, CO2 partial pressure, solid-liquid ratio, and agitation speed were investigated in the boron extraction from the ore. As a result of the experimental studies, it was found that the leaching rate increased with the rise in the reaction temperature and CO2 partial pressure, and decreased with the increase in the particle size and solid-liquid ratio. The reaction temperature was found to be a significant parameter affecting the leaching rate, which varied from 13% to 97% between 303 and 393 K. Agitation speed appears to have no significant effect on the leaching rate. By using several empirical kinetic models to correlate the experimental data, it was found that the leaching rate fits to the Avrami Model. The activation energy of the process is found to be 21.1 kJ.mol(-1).
Keywords: Ulexite; leaching kinetics; CO2 partial pressure; Avrami Model; DISSOLUTION KINETICS; BORIC-ACID; COLEMANITE; EXTRACTION; Engineering